Pearls: Seperangkat Alat Monitoring dan Evaluasi Kinerja Keuangan Koperasi Kredit - Yuli Kurniyati (Jurnal Maksipreneur, 2011)
Pearls is a system of 44 financial ratios which the World Council of Credit Unions (WOCCU) employs to provide a detailed picture of credit union operations. Standing for Protection, Effective Financial Structure, Asset Quality, Rates of Return, Liquidity, and Signs of Growth, the Pearls system was originally designed and implemented with Guatemalan credit unions in the late 1980s. WOCCU now uses it worldwide to monitor the performance of credit unions, to create a universal language that each credit union can speak and understand, to generate comparative credit union rankings, and to provide the framework for a supervisory unit at the second tier. Also, Pearls presents financial variables upon which credit unions can base their business planning. In essence, Pearls was designed first as a management tool, and later became an effective supervisory mechanism.